Pengaruh Budaya Organisasi, Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan Generasi Z di Kabupaten Bekasi - Muhamad Supriyadi; Dwi Auli Ramadhania; Ramdhan Dwi Kurnia; Bayhaqi; Dede Aditya; Sunita Dasman (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the influence of organizational culture, leadership style, and work motivation on the performance of Generation Z employees in Bekasi Regency. A quantitative approach using a survey method was employed. Primary data were collected by distributing Likert-scale questionnaires to 45 respondents—Generation Z employees in Bekasi Regency—selected via purposive sampling. Data analysis was conducted using IBM SPSS Statistics, involving validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²) test. The results indicate that, individually (partially), organizational culture has a positive and significant effect on employee performance, with a significance value of 0.011 (<0.05). Conversely, leadership style and work motivation do not significantly affect employee performance, as their respective significance values ​​were 0.260 and 0.271 (>0.05). However, when analyzed simultaneously, organizational culture, leadership style, and work motivation collectively have a significant effect on employee performance, with a significance value of 0.000 (<0.05). The coefficient of determination test yielded an R² value of 0.549, meaning that 54.9% of the variation in employee performance can be explained by these three independent variables, while the remaining 45.1% is influenced by factors outside the scope of this study. These findings indicate that organizational culture is the most significant factor in enhancing the performance of Generation Z employees in Bekasi Regency.